Physical cues in biomaterials modulate macrophage polarization for bone regeneration: a review - Yang, Tianxiao; Fang, Zhurun; Zhang, Jin; Zheng, Shengnai (Frontiers in Bioengineering and Biotechnology, 2025)
Bone regeneration is a complex process governed by inflammation, angiogenesis, and tissue remodeling. Macrophages play central roles by dynamically shifting between pro-inflammatory (M1) and anti-inflammatory (M2) phenotypes. While biochemical signals have been widely studied, emerging evidence highlights the immunomodulatory potential of physical cues from biomaterials. This review summarizes macrophage functions across bone healing phases and critically examines how physical cues—such as stiffness, topography, pore architecture, hydrophilicity, electromagnetic stimuli, and metal composition—modulate macrophage polarization. We discuss underlying mechanosensing mechanisms, phenotype plasticity, and the dynamic interplay between materials and immune cells. Finally, we highlight current limitations and propose future directions to guide the design of next-generation osteo-immunomodulatory biomaterials.